Loyalitas dan Kepuasan Penumpang Kereta Api Argo Parahyangan - Agus Triono; Masjraul Hidayat; Aswanti Setyawati; Susanty Handayani; Yana Tatiana (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This research aims to measure service quality and timeliness which has an impact on passenger loyalty and passenger satisfaction on the Argo Parahyangan train. Some problems, such as the frequency of use of the Bandung-Jakarta Argo Parahyangan Railway transportation services, have not shown a minimum limit every weekend. There is still a difference between the departure and actual arrival of the Argo Parahyangan train against the schedule that has been set. The arrangement of the operating plan has not been maximized due to limited facilities. Research with a sample of 89 respondents and data analysis method using the method of path analysis. The results show that passenger satisfaction can mediate the indirect effect of service quality on passenger loyalty. Passenger satisfaction is able to mediate the indirect effect of punctuality on passenger loyalty. The key finding of this research is the perception of passengers who feel they have never received other services as comfortable as rail transportation and state that they will not switch to using rail transportation.